Efektivitas Terapi Accupressure Titik Hegu Dan Aromaterapi Lemon Terhadap Kualitas Hidup Pasien Kanker Serviks Yang Menjalani Kemoterapi - Ardiyanti, Anis; Intan Sari, Rinda; Pramusinta, Linda (NHM PRESS, 2024)
Cervical cancer is a type of cancer that can cause death, so chemotherapy is needed, this can affect the quality of life. The purpose of this study was to determine the effectiveness of hegu point acupressure therapy with lemon aromatherapy on the quality of life of patients. This study used a quasi-experimental two group pre-post test design with the criteria of women with cervical cancer undergoing chemotherapy. The results of the study obtained the characteristics of the respondents who were mostly elderly, unemployed, stage III. The results of the statistical test obtained a p value of 0.000, meaning that there was a relationship between the provision of hegu point acupressure and the quality of life of cervical cancer patients and 0.000, meaning that there was a relationship between the provision of lemon aromatherapy and the quality of life of cervical cancer patients. However, the results of the difference test obtained a p value of 0.543, meaning that there was no difference in the effect between the provision of hegu point acupressure and the provision of lemon aromatherapy on the quality of life of cervical cancer patients. In conclusion, both of these therapies can be given to cervical cancer patients undergoing chemotherapy with quality of life. Suggestions for further researchers to add variables and the number of respondents.